«Green» employment: the essence and genesis of the concept - N. A. Nenastev; N. N. Yashalova (Вестник университета)
The article is devoted to the generalization and systematization of the theoretical knowledge accumulated to date in the field of «green» (environmental) employment. Two key aspects of the relevant problem are touched upon: the definition of the term under consideration and the main stages of the environmental employment periodization. The study is based on analysis and synthesis, generalization, as well as economic-historical and comparative methods. The analysis includes significant fundamental Russian and foreign scientific works on the subject under study. A review of approaches to the definition of environmental employment is presented, its special characteristics and features. Based on the analysis and generalization of scientific and specialized research, the author’s definition of «green» employment has been developed, which should be understood as labor activity associated with «green» transformation and increasing the environmental sustainability of economic activities that have a high anthropogenic impact on the environment.